Prepare for trouble and make it double: Effects of Carpobrotus acinaciformis and Apis mellifera invasion in floral visitor networks - Luiz F. C. Serigheli; Sofia Bacca; Brisa Marciniak; Michele S. Dechoum (NeoBiota)
Invasive species pose a significant threat to ecological systems, impacting biodiversity and ecosystem functioning. Invasive plants and bees can alter mutualistic networks by increasing nestedness and reducing modularity, as a consequence leading to a reduction in network biodiversity and specialization. In this study, we investigated the ecological consequences of invasion by the non-native plant Carpobrotus acinaciformis and the non-native bee Apis mellifera, as well as the effects of controlling the invasive plant species on bee-plant interaction networks in coastal ecosystems. Our hypothesis is that C. acinaciformis, a melitophilous invasive plant, and A. mellifera, a generalist forager, both influence interaction networks, and that their control can alter network structure. Fieldwork was carried out in the Dunas da Lagoa da Conceição Natural Municipal Park, in southern Brazil, with active searches and collection of bees and flowering plants in areas invaded and uninvaded by C. acinaciformis in year 1 of the study. Collection procedures were repeated in uninvaded and managed areas after C. acinaciformis was subjected to mechanical control in year 2. We compared interaction network metrics between invaded and uninvaded areas in year 1 and between managed and uninvaded areas in year 2 using null models. We also simulated the elimination of A. mellifera from all networks (invaded, uninvaded, and managed) as a first step to understanding the effects of invasive honey bees. This simulation suggests that A. mellifera invasion increases nestedness and reduces modularity of the interaction networks. The elimination of the invasive plant and the simulated removal of the invasive bee led to changes in network dynamics, suggesting potential shifts that increased the stability and specialization of interaction networks. Our findings contribute to the understanding of the intrinsic interactions between invasive species such as C. acinaciformis and A. mellifera and native bee-plant networks. We emphasize the need for long-term studies using multiple methodologies, including field experiments and simulations, to generate comprehensive assessments for building knowledge on biological invasions and management. This enables adaptive and effective management strategies to mitigate the impacts of invasive species on ecosystem dynamics and biodiversity conservation.